The hostile environment in primary care: Qualitative analysis of a cross sectional survey of health care professionals in primary care - Joanna Dobbin; Francesca Burns; Sebastian Casalotti; Mariam Jaffer; Monica Sharman; Catarina Soares; Josie Reynolds (Elsevier, 2024)
Background: In 2014 the UK government rolled out the then called hostile environment as a series of punitive policies designed to disenfranchise undocumented migrants from living in Britain. As part of these measures upfront charging was introduced in 2017 which saw patients being denied treatment without prior full payment based on their immigration status. Aim: Assess the knowledge of the charging regulations in a sample of primary care practitioners. Assess the impact of the regulations on both patients and practitioners in a primary care setting. Methods: Building on a previous survey by the RCPCH, a cross sectional survey was circulated through the RCGP faculties and GP training groups within England. Demographic information and likert responses were collected from over 300 responses. Thematic analysis of over 120 white space questions was undertaken to create themes and sub-themes. Results: Results showed an overall poor knowledge of the regulations. Thematic analysis was split into two main categories, (i) human impact of the policies and (ii) the economic and political impact of the policies. Key points were (i) lack of knowledge and awareness of the regulations, (ii) evidence of patient harm through patients' being denied care, avoiding care or having care delayed, (iii) evidence of clinician harm through burnout, stress, a loss of faith in practice and concerns over extra work and (iv) concerns over implicit bias and structural racism within primary care and (v) concerns over lack of economic analysis. Conclusion: Charging of overseas visitors is poorly understood within primary care despite having an impact on both patients and practitioners within this setting. Recommendations to help tackle this issue and reduce harm include training of staff, systematic reporting of harm, and a system wide economic analysis.